Functional subsets of human helper-inducer cells defined by a new monoclonal antibody, UCHL1. - Smith, S; Brown, M; Rowe, D; Callard, R; Beverley, P (1986)
The monoclonal antibody UCHL1 identified an antigen present on most thymocytes, a subpopulation of resting T cells within both the CD4 and CD8 subsets, and on mature activated T cells. The UCHL1 determinant is also present on cells of the myeloid lineage, but not normal B cells or NK cells. Functionally, UCHL1 identifies a subpopulation of T cells which proliferates maximally to soluble antigen and provides maximum help for PWM-stimulated immunoglobulin synthesis. In contrast, the UCHL1- cells do not induce immunoglobulin synthesis and do not proliferate in the presence of soluble antigen, although both the UCHL1- and the UCHL1+ fractions of T cells proliferate well in the presence of PHA. By standard immunoprecipitation techniques and SDS page, the antigen recognized by UCHL1 was found to have a molecular weight of 180,000-185,000. Preclearing experiments using antibodies identifying the leucocyte common antigen, LCA, and the lymphocyte function-associated antigen, LFA-1, which have similar molecular weights to UCHL1, showed that the UCHL1 determinant is not biochemically related to these antigens.